Usefulness of expanding the indications of early rescue intracytoplasmic sperm injection. (13th December 2021) - Shibahara, Takashi; Fukasaku, Yuu; Miyazaki, Nozomi; Kawato, Hiroaki; Minoura, Hiroyuki
Abstract: Purpose: Early rescue intracytoplasmic sperm injection (ICSI) is often performed in cases in which not even a single oocyte has extruded a second polar body 6 h after insemination. We evaluated the usefulness of expanding the indications of early rescue ICSI to cases in which <80% of oocytes have extruded second polar bodies 6 h after insemination. Methods: Early rescue ICSI was performed on oocytes that were denuded 2.5 h post‐insemination and whose extrusion of the second polar bodies had been examined 6 h post‐insemination with a PolScope. Results: In vitro fertilization was performed on 24 496 oocytes of 4944 cycles, and 1438 cycles had <80% rate of the second polar body extrusion. Rescue ICSI was performed on 3933 oocytes. Three pronuclei (3PN) incidence of rescue ICSI was 3.0% in oocytes with ≥50% rate of the second polar body extrusion. With respect to the second polar body extrusion rate, no differences were observed in normal fertilization, blastocyst development, implantation, miscarriage, or live birth rates for rescue ICSI. Conclusion: By expanding the indications of early rescue ICSI using the PolScope to cases in which <80% of oocytes have extruded the second polar bodies, many fertilized oocytes can be obtained without considerably increasing the 3PN rate. Abstract : Evaluation of the usefulness of expanding indications of eary rescue ICSI to case where <80% of oocytes have released second polar bodies 6 h after insemination. By expanding indivations of early resucue ICSI using the Polscope, many fertilized oocyte are obtained without greatly increasing the 3PN rate.